Analisis Fundamental Makro Terhadap Kinerja Keuangan dan Struktur Modal, Manajemen Laba, Karakteristik Perusahaan Sebagai Variabel Intervening Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Rivaldo Martadinata Anthonie; Hwihanus Hwihanus (Universitas Katolik Widya Karya Malang, 2024)
This research investigates the impact of macroeconomic fundamentals on financial performance and capital structure, with earnings management and firm characteristics as intervening variables, focusing on manufacturing companies listed on the Indonesia Stock Exchange. The macroeconomic fundamentals analyzed include inflation, exchange rates, GDP, and interest rates, which are hypothesized to affect stock returns. Capital structure is measured by the debt-to-equity ratio and the debt-to-asset ratio. Financial leverage is gauged using the interest coverage ratio and the debt-to-operating income ratio. Firm characteristics encompass the company's age, the number of board commissioners, the number of directors, and the number of audit committee members. Financial performance is evaluated using indicators such as EBIT, DFL, DOL, DPR, asset turnover, and EPS growth. The research employs a quantitative method with data analysis conducted using Smart PLS. The results indicate that financial leverage significantly influences firm characteristics and capital structure but does not significantly impact financial performance. Macroeconomic fundamentals significantly affect firm characteristics but do not significantly impact financial performance, earnings management, or capital structure. Firm characteristics significantly influence financial performance but not earnings management. Capital structure significantly affects earnings management but does not significantly impact financial performance. This study aims to provide insights for decision-makers to enhance company financial performance through effective management of capital structure and earnings management.